Federal Republic of Nigeria Early Childhood Development : SABER Country Report 2013 - World Bank (Washington, DC, 2014)
This report presents an analysis of the Early Childhood Development (ECD) programs and policies that affect young children in Nigeria and recommendations to move forward. This report is part of a series of reports prepared by the World Bank using the SABER-ECD framework and includes analysis of early learning, health, nutrition and social and child protection policies and interventions in Nigeria, along with regional and international comparisons. Data on ECD policies and programs were collected through the SABER-ECD exercise in Bauchi, Ekiti, Kwara, and Oyo states. The SABER-ECD initiative is designed to enable ECD policy makers and development partners to identify opportunities for further development of effective ECD systems. This Country Report presents a framework to compare Nigeria s ECD system with other countries in goals and corresponding nine policy levers are examined in detail and some policy options are identified to strengthen ECD services that are offered. Table 15 summarizes the key policy options identified to inform policy dialogue and improve the provision of essential ECD services in Nigeria to ensure that all young children have a strong start in life and the opportunity to reach their full potential.